La reproducción de los oficios. De la organización gremial a la Escuela Nacional de Artes y Oficios de Hombres en la ciudad de México, 1780-1915 - Pérez Toledo, Sonia (El Colegio de México, A.C., 2021)
With the 18th Century reforms to guilds and the 1813 decree on the freedom of trades, artisanal corporations broke apart in many different fashions, but this did not modify the hierarchical structure and the role of the master craftsman in the apprenticeship process. After independence, legislation did not involve regulations on the organization of trades until 1857, but some members of the elite voiced the need to support artisans and stimulate the “correct” teaching of trades. Politicians and labor organizations advocated for the creation of government-run trade schools, but conditions at the time were an obstacle to the promotion of occupational education. In 1867, the National Men’s School of Arts and Trades was founded in Mexico City, which functioned with difficulty, but constantly, until 1915.Nevertheless, the evidence shows that this institution, like others of its kind, failed in its purpose and was unable to displace the master craftsman in this role. It is argued that the traditional, social nature of the apprenticeship process allowed it to occupy a fundamental place in the education of workers given the incapacity of the liberal state, and so the period of study was lengthened and political and elite discourses are contrasted with information on the trade school’s social importance, taken from little- studied primary sources, in dialogue with the historiography.